2015
DOI: 10.1080/23744006.2015.1033154
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia and violence: realities and recommendations

Abstract: Published findings on the relationship between schizophrenia and violence have been mixed, due to differences in study design and quality. In this review, we address the issue with an emphasis on characterizing who is most likely to be violent and when. We conclude that: (1) individuals with schizophrenia are at an increased risk for violence due to specific psychotic symptoms; (2) this risk is increased by brain abnormalities, psychiatric comorbidities, and demographic factors that are not specific to schizop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1
3

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 109 publications
1
17
1
3
Order By: Relevance
“…Taken together, these findings suggest that paranoid individuals possess the same level of functional skill as non-paranoid individuals but that the implementation of these skills in real-world settings is disrupted. Increased paranoid ideation among individuals with schizophrenia has previously been linked to greater incidences of violent behavior (Nestor, 2002; Silverstein et al, 2015), but this is the first time of which we are aware that paranoia has been linked to difficulties with more normative day-to-day function. Paranoia may therefore worsen the social impairments that are generally experienced by individuals with schizophrenia.…”
Section: Discussionmentioning
confidence: 86%
“…Taken together, these findings suggest that paranoid individuals possess the same level of functional skill as non-paranoid individuals but that the implementation of these skills in real-world settings is disrupted. Increased paranoid ideation among individuals with schizophrenia has previously been linked to greater incidences of violent behavior (Nestor, 2002; Silverstein et al, 2015), but this is the first time of which we are aware that paranoia has been linked to difficulties with more normative day-to-day function. Paranoia may therefore worsen the social impairments that are generally experienced by individuals with schizophrenia.…”
Section: Discussionmentioning
confidence: 86%
“…Of particular concern is the evidence showing an increased risk of aggressive and violent behavior (severe assaults, attempted murder, homicide) among people with schizophrenia compared to the general population. 2 6 Although most people with schizophrenia are not violent, 7 , 8 individuals suffering from schizophrenia were found to be 2.1–4.6 times more likely to commit a violent crime or engage in violent behavior than the general population, even when taking into account socioeconomic status (SES), comorbid substance use, and personality disorders. 2 , 9 , 10 In addition to promoting stigmatization and victimization of all persons with mental health problems, 11 violent behavior by persons with schizophrenia has important consequences for the health and criminal justice systems, as shown by increasing numbers of forensic hospitals, longer periods in hospital, 12 , 13 and increased rates of incarceration, 14 all of which increase costs.…”
Section: Introductionmentioning
confidence: 99%
“…The literature has shown that among patients with schizophrenia and first episode psychosis (FEP), the presence of isolated dynamic risk factors such as substance abuse or dependency (Fazel et al, 2009;Large, 2014;Latalova, 2014;Vacheron & Cornic, 2010), antisocial personality disorders (APDs) (Putkonen, Kotilainen, Joyal, & Tiihonen, 2004) or positive psychotic symptoms (Elbogen & Johnson, 2009;Lincoln, Lüllmann, & Rief, 2007;Nolan et al, 2005;Swanson et al, 2006;Witt, Lichtenstein, & Fazel, 2015) increases the risk of VB. More recently, several studies have shown that lack of insight (Bjørkly, 2006;Foley et al, 2005;Reinharth, Reynolds, Dill, & Serper, 2014;Verma, Poon, Subramaniam, & Chong, 2005;Voyer, Jaafari, & Senon, 2011) and the presence of impulsivity (Bjørkly, 2013) could also play a critical role in the risk of VB in schizophrenia and FEP (Bjørkly, 2013;Nielssen et al, 2012;Silverstein et al, 2015;Volavka & Citrome, 2008;Witt et al, 2013). In addition, various studies have shown that the levels of these factors may differ among subgroups of violent patients with chronic schizophrenia and a range of psychopathological profiles have been identified on this basis.…”
mentioning
confidence: 99%